Factors Associated with the Utilization of the Elderly Posyandu in the Working Area of the Muara Saung Health Center, Kaur District in 2022 - Saputra, Yopi; Rohani, Tuti; Darmawansyah, Darmawansyah (Universitas Dehasen Bengkulu, 2022)
The elderly are an aging population and require a process of adaptation to various changes in function and environmental stress caused by a decrease in the body's ability (Listyarini & Alvita, 2018). In the world, the number of elderly people ranges from ≥629 million people (Susanti, Mila, 2017). According to data from the Central Statistics Agency (BPS), the number of pre-elderly and elderly people in Kaur Regency in 2021 will be 130,266 people (BPS, 2021). According to the health profile of Kaur Regency in 2021, only 11,7204 elderly people receive health services out of a target number of 130,266 people in the working area of the Muara Saung Health Center and is the lowest in Kaur District. The aim of this research is to find out the factors related to the utilization of the elderly posyandu in the working area of the Muara Saung Health Center, Kaur Regency in 2022. This study used a quantitative method with a cross-sectional study design. The population in this study were all elderly people at the Muara Saung Health Center in Kaur Regency in 2021, with a total of 288. The sample was taken in this study using the Simple Random Sampling technique. The number of samples used in this study were 74 respondents. The results of this study indicate that there is a relationship between the level of knowledge and the utilization of the elderly posyandu in the working area of the Muara Saung Health Center, Kaur Regency, in 2022 with a value of p = 0.017. there is a relationship between family support and the use of the elderly Posyandu in the working area of the Muara Saung Health Center, Kaur Regency in 2022 with a value of p = 0.008. There is a relationship between the role of cadres and the utilization of the elderly posyandu in the working area of the Muara Saung Health Center, Kaur Regency in 2022 with a value of p=0.023. Suggestions can add insight in the health sector, especially regarding the elderly posyandu at the Muara Saung Health Center, Kaur Regency